2023
DOI: 10.1371/journal.ppat.1011072
|View full text |Cite
|
Sign up to set email alerts
|

Insect egg-induced innate immunity: Who benefits?

Abstract: Plants perceive the presence of insect eggs deposited on leaves as a cue of imminent herbivore attack. Consequential plant signaling events include the accumulation of salicylic acid and reactive oxygen species, transcriptional reprogramming, and cell death. Interestingly, egg-induced innate immunity shows similarities with immune responses triggered upon recognition of microbial pathogens, and in recent years, it became apparent that egg perception affects plant–microbe interactions. Here, we highlight recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…A study by (Peñaflor et al, 2011) found that oviposition by FAW on maize plants was associated with a decreased emission of constitutively emitted volatiles as well as a suppression of those that are induced upon herbivory. Suppression of plant defenses by insect eggs has also been reported for Arabidopsis (Bruessow et al 2010), although the opposite may also be the case (Stahl et al, 2023). In our case, we observed decreased emission of constitutive compounds in the MD as well as the MD + OS treatment.…”
Section: Discussionsupporting
confidence: 81%
“…A study by (Peñaflor et al, 2011) found that oviposition by FAW on maize plants was associated with a decreased emission of constitutively emitted volatiles as well as a suppression of those that are induced upon herbivory. Suppression of plant defenses by insect eggs has also been reported for Arabidopsis (Bruessow et al 2010), although the opposite may also be the case (Stahl et al, 2023). In our case, we observed decreased emission of constitutive compounds in the MD as well as the MD + OS treatment.…”
Section: Discussionsupporting
confidence: 81%